Psychological Features of the Relationship Between Hardiness and Coping Behavior of the Individual - Predko, Viktoriia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
The article reveals the concept of coping behavior, its features, and its main functions in the life of a person. It is presented as a special type of social behavior that ensures the preservation of the mental health and well-being of the individual and helps to cope with stressful events and difficult life situations with the help of conscious actions. The main ways of coping behavior are characterized. It is emphasized that an important factor in the formation of coping behavior is the adaptive potential of the individual, namely the level of its hardiness. It is emphasized that it is the hardiness of the individual that is the leading factor in the effective life of the individual, which provides the ability to productively overcome difficulties, using constructive behavioral strategies, to cope with difficult life situations and psychological stress. It helps to minimize the negative consequences, turning them into new opportunities for one’s development, and most importantly, to maintain harmonious communication with the environment. The article also presents the results of a study of the features of the relationship between hardiness and the coping behavior of an individual. Among the features of the manifestation of methods of coping behavior in the subjects, a high level was found among such indicators as self-control, flight avoidance, and positive reassessment. The study established a relationship between coping behavior and personality resilience. In particular, the presence of a direct statistically significant correlation of medium strength (r=0.390, sig=0.012) between the "Problem Solving Planning" strategy and hardiness was revealed; the presence of a direct statistically significant relationship of average-strength (r=0.388, sig=0.013) between the "Self-control" strategy and hardiness; the presence of a direct statistically significant relationship of medium strength (r=0.463, sig=0.000) between the "Taking responsibility" strategy and hardiness; the presence of an inverse statistically significant relationship of average-strength (r=-0.429, sig=0.000) between the "Escape-avoidance" strategy and hardiness. Peculiarities of expressiveness of ways of coping behavior in the subjects with high and low hardiness were determined. Thus, a group of people with a high level of hardiness is characterized by the manifestation of constructive skills to resist difficulties, energy, and the ability to defend their interests, minimize their anxiety and positively reassess the current situation. At the same time, individuals with low levels of hardiness are more inclined to be attracted by the support of others than to solve problems on their own, they tend to use an escape-avoidance strategy, often distance themselves, and show low self-control and low ability to solve problems.